Studi Living Qur’an dalam Tradisi Kliwonan Santri PP. Attauhidiyyah Syekh Armia bin Kurdi Tegal - Itmam Aulia Rakhman (Sekolah Tinggi Ilmu Tarbiyah (STIT) Pemalang, 2019)
One of the socio-religious phenomena in Tegal Regency which is able to become a magnet for the community is the Tradisi Kliwonan in the PP. Attauhidiyyah Sheikh Armia bin Kurdi Tegal, in the form of the Akbar and Istigasah Kubra. In this tradition there is a reading of the letter and fragments of the verses of the Qur'an which are atomistic, so the author feels the need to conduct research with the Living Qur'an method in order to reveal the meaning of the santri Attauhidiyyah's interaction with the Qur'an as its holy book.This research is field research. The approach taken is the socio-anthropological approach. Whereas to analyze the data that has been collected, the researcher uses the hermeneutic (interpretative) paradigm as one of the living paradigms of the Qur'an. The results of the study revealed that social receptions to the Qur'an in the Tradition of the Kliwonan inPP. Attauhidiyyah Sheikh Armia bin Kurdi Tegal, found in: (1) Reading of Yasin Faḍilah Letter (2) Recitation of al-Fātihah (3) Reading of certain verses during the implementation of the Istigasah and Prayer together.